Women in handball - Platen, P. (Education. Physical training. Sport, 2002)
Some words about women-specific topics in team handball: Concerning injuries risk profile of female players is different from that of their male counterparts. A female player has a risk of approximately one injury per 480 hours of handball training and games. More than one half of all injuries are located at the lower extremities:, one third are in the upper extremities approximately 6% at the trunk and 8 % at the head. Players most often suffer from injuries of the ankle joint, followed by the finger joints, rupture of the anterior cruciate ligament. meniscus lesions, elbow joint and tendinitis of the shoulder. Interestingly, there is an increase of injuries; with ongoing season indicating a relation between the injury rate and the aerobic capacity, which declines at the end of the season. All 5 principal components of motor fitness are expected differently in team handball, regardless of gender. From an energetical point of view. a handball match and the corresponding training might be classified as a combination of an endurance- and a speed-discipline. Short sprints, explosive movements and changes of movement directions in the attack (fakes) and the defence. as well as throwing and jumping mainly stress the anaerobic-alactacid energy expenditure (e.g. ATP-resvnthesis from creatine-phosphate). The anaerobic-lactacid energy expenditure rnainly is involved in long sprints: (counter) and sprints with only short brakes as well as in powerful physical actions in attack and defence (stress situations in the match). Aerobic metabolism and fatty acid and glucose oxidation) is the basical function of handball-specific performance. Data on aerobic capacity of German I and II division teams during different times of the season as well as values of rnaximal acceleration speed and maximal cyclical speed will be shown during the presentation.